2001
DOI: 10.1053/jhep.2001.27563
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hepatitis B virus DNA breakthrough in patients receiving prolonged lamivudine therapy

Abstract: Factors associated with hepatitis B virus (HBV) DNA breakthrough and the significance of YMDD variants without the presence of wild-type YMDD during prolonged lamivudine treatment are unknown. We studied the amino acid sequence of codon 552 (YMDD motif) and codon 528 by means of a line probe assay in 159 chronic HBV patients (median follow-up 29.6 months). Pretreatment HBV DNA levels and alanine transaminase (ALT) levels correlated inversely with the time to HBV DNA breakthrough with YMDD variants (r ‫؍‬ ؊0.46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
275
8
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(312 citation statements)
references
References 25 publications
25
275
8
4
Order By: Relevance
“…14,15 Previous studies with LAM and telbivudine demonstrated a positive correlation between early profound HBV suppression and long-term clinical outcome. 25,31,32 Our study also showed that virological responses to ETV at week 12 of treatment determined the degree of HBV DNA reduction over 48 weeks, regardless of previous antiviral drug resistance.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…14,15 Previous studies with LAM and telbivudine demonstrated a positive correlation between early profound HBV suppression and long-term clinical outcome. 25,31,32 Our study also showed that virological responses to ETV at week 12 of treatment determined the degree of HBV DNA reduction over 48 weeks, regardless of previous antiviral drug resistance.…”
Section: Discussionsupporting
confidence: 56%
“…23 Studies with LAM or ADV suggested that the presence of high pretreatment HBV DNA levels was a risk factor for increased antiviral drug resistance and attenuation of virological response in treatment-naïve or LAM-resistant patients. 24,25 In the current study, pretreatment serum HBV DNA levels were lower in LAMr/ADVr patients. Given that pretreatment low viral load is predictive of HBe seroconversion, 26 it was interesting to note that the rate of HBeAg loss (including seroconversion) after ETV monotherapy was no higher in LAMr/ADVr patients (with lower pretreatment viral loads) than in LAMr patients.…”
Section: Discussionmentioning
confidence: 45%
“…Both interferon and reverse transcriptase inhibitors are used to treat chronic HBV infection [31][32][33]. Although there is no cure for HBV infection, these treatments manage infection, preventing viral replication, leading to a lowered viral load and amount of virus in the blood.…”
Section: Birth 90%mentioning
confidence: 99%
“…5 Monitoring for primary nonresponse is important because a high residual viral level after the first 6-12 months of therapy has been demonstrated to be associated with increased risk of antiviral resistance. [6][7][8] (ii) Secondary Antiviral Treatment Failure (or Virologic Breakthrough). Virologic breakthrough, which is usually associated with drug resistance, is defined as a Ն1 log 10 IU/ml increase in serum HBV DNA level from nadir in two consecutive samples 1 month apart in patients who have responded and have been compliant with antiviral medication(s).…”
Section: (A) Clinical Classification Of Antiviral Resistancementioning
confidence: 99%